Crime prevention through landscape design in public park - Mohd Zuki, Muhammad Zukhairi; Ibrahim, Putri Haryati (2016)
This study aimed on how crime can be prevented and fear of crime can be minimized through landscape design in the public park. The study focused on the element of the landscape design that can prevented crime based on the safe city program by Town and Country Planning Department. Although numerous studies have examined on crime prevention, extra attention needs to be given to the aspect of the element of the landscape design to ensure its sustainability. To obtain information on the element of landscape design that can prevented crime rate, questionnaires survey was distributed to user at Taman Jaya (n= 84) and Taman Aman (n=81). The study found that the availability of park, lack in term of the landscape element are the main problem that government should provide a better service to the public. This study has recommended several measure to address this issues such as provide the good landscape design that can help to reduce crime and minimized fear of user in the park